EFFECT OF CORPORATE SOCIAL RESPONSIBILITY ON THE CUSTOMER SATISFACTION OF SELECTED DEPOSIT MONEY BANKS IN ABUJA, NIGERIA - Obubele Tamuno, Faustina; Yimi Bagobiri, Esther (African Journal of Social and Behavioural Sciences, 2025)
his study examines the influence of corporate social responsibility (CSR) on customer satisfaction in selected deposit money banks in Abuja, Nigeria, specifically Access Bank, Zenith Bank, UBA, GT Bank, and First Bank. Using a survey research design, data were collected from 425 customers, selected through stratified random sampling. The Fisher formula guided the determination of sample size. Correlation and regression analyses were employed to test the study’s hypotheses. The results indicate that CSR has a significant and positive impact on customer satisfaction. Specifically, both the economic and legal responsibilities of banks were found to enhance customer satisfaction significantly. The study concludes that strengthening economic and legal responsibilities can further improve customer satisfaction among bank customers in Abuja.